"Making a Difference": Unpacking the Positives in Correctional Work and Prison Life From the Perspective of Correctional Workers. (June 2023) - Ricciardelli, Rosemary; Johnston, Matthew S.; Maier, Katharina
Prisons are rarely conceptualized as promoting "positivity" in the lives of people who are incarcerated (PWAI) or correctional workers (CWs). Analyzing data from 908 open-ended survey responses of Canadian provincial and territorial correctional employees, we present nuances to the more negative constructions of carceral environments; namely, that many CWs work to better the lives of marginalized and vulnerable criminalized people. CWs are able to reflect on how their occupation facilitates personal growth and the pursuit of social and transformative justice. We discuss how their internal commitments toward rehabilitating and making a difference must be reinforced through institutional and organizational changes.